Supernatural beings from Slovenian myth and folktales - Kropej, Monika (Studia Mythologica Slavica Supplementa, 2012)
Focusing on Slovenian mythology the book contains a review of Slovenian mythological, historical, and narrative material. Over 150 supernatural beings are presented, both lexically and according to the role that they have in Slovenian folklore. They are classified by type, characteristic, features, and by the message conveyed in their motifs and contents. The material has been analysed in the context of European and some non-European mythological concepts, and the author deals with theory and interpretations as well as the conclusions of domestic and foreign researchers. The book forms new starting points and a classification of supernatural beings within a frame of a number of sources, some of which have been published for the first time in this book.